A critical review of the odonate fauna of Trentino: annotated check-list and new relevant data for Italy (Insecta: Odonata) - Assandri, Giacomo (Fragmenta entomologica, 2019)
By the first half of the Twentieth Century, the Odonate fauna of Trentino (Oriental Alps, Italy) was quite well known; subsequently, few surveys on dragonflies were carried out, resulting in a limited update of the knowledge on this taxon. The aim of this study is to provide a critical and annotated check-list of the Odonata of this province for the period from 1851 to 2018. This synthesis is based on a total of 3814 records obtained from the literature (955 records), revision of collections (1048 records), and unpublished recent data (1811 records). An updated and comprehensive Odonatological bibliography of the region is also provided. Overall, sixty-one species were confirmed to occur (or have occurred) in Trentino. These represent the 64% of the species recorded in Italy and the 43% of the species recorded in Europe. Presence of five additional species (Ceriagrion tenellum, Coenagrion lunulatum, C. ornatum, Ophiogomphus cecilia, and Epitheca bimaculata) should be considered doubtful for Trentino. Further two species (Platycnemis latipes and Onychogomphus uncatus) have to be excluded from the fauna of the study area. Fifty-four species were recorded also after 2000, whereas seven species were not confirmed after this year (Lestes dryas, L. virens, L. barbarus, Sympecma paedisca, Coenagrion scitulum, Brachytron pratense, and Sympetrum flaveolum). Several new records resulting from this study (referred to: Erythromma najas, Aeshna subarctica, Aeshna caerulea, Aeshna grandis, Leucorrhinia pectoralis) have a conservation or biogeographical relevance which transcends the borders of the study area, being noteworthy from an Italian or Alpine perspective and are thus commented in detail. Taxonomic notes on subspecies are also given when relevant.